ANALISIS TIAMFENIKOL DALAM SIRUP KERING DAN DEGRADASINYA PADA SUHU YANG BERBEDA MENGGUNAKAN METODE KCKT - Giani Khairunnisa, Cantika; Vandian Nur,, Achmad; Santika Rahmasari, Khusna; Bagus Pambudi, Dwi (UIR Press, 2025)
Thiamphenicol is a broad-spectrum antibiotic that works similarly to chloramphenicol.Thiamphenicol is formulated as a dry syrup because it is unstable in water, where the amide group can undergo hydrolysis. This study aimed to determine the impact of temperature and storage time on the drug content in thiamphenicol dry syrup. The study involved physical stability testing by observing organoleptic changes and pH testing. Chemical stability was assessed by measuring drug content using HPLC (High Performance Liquid Chromatography) with a mobile phase of aquabides and methanol (4:1). The sample preparation involved storing thiamphenicol dry syrup for 7 days at room temperature (15 - 30ºC) and cold temperature (2 - 8ºC). The results indicated that temperature and storage time did not affect the physical stability during the storage period. However, a significant decrease in drug content was observed: at room temperature, a reduction of 37,20% in sample 1 and 54,57% in sample 2; at cool temperature and at cold temperature, a reduction of 29,73% in sample 1 and 24,73% in sample 2. Statistical analysis using One Way ANOVA showed significant values of 0.000 < 0.05 for sample 1 and 0.001 < 0.05 for sample 2, indicating that temperature differences significantly affect the thiamphenicol content. The results demonstrate that temperature and storage time have a significant impact on the chemical stability of thiamphenicol dry syrup.